PELAKSANAAN PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI SMP NEGERI KOTA SOLOK - Afrino, Afrino; Atmazaki, Atmazaki,; Tressyalina, Tressyalina (Universitas Negeri Padang, 2018)
ABSTRACTThe purpose of this research are three (1) to describe the process of implementatiom of text-based Indonesian language learning, (2) to describe the process of teaching and learning of text-based Indonesian language focused on learning materials, (3) to describe the process of text learning based on the learning method. This research type is qualitative research by using descriptive method. Technique of data collecting is done by observation, interview, and documentation study. The result showed that teachers of SMP Negeri 1, SMP Negeri 2 Solok, and SMP Negeri 4 Solok have implementated four aspects ofe text-based learning that is at the stage of building the context, studying the model text, constucting guided and constructing independently. The materi used in the three schools are learning material with excellent categories. Teaching materials are chosen and determined with consideration and attention to problems, including (a) the objectives to be achieved so that they are relevant, (b) the level of students' thinking abilities, (c) the scope and the sequences need to be arranged so that they are systematic and obvious, and (d) time and equipment are also considered. The use of learning methods in the three schools is also good in terms of its effectiviness, its relevance to learning, up to the use of the method itself. Kata kunci : pelaksanaan pembelajaran bebasis teks, materi pembelajaran, metode pembelajaran